Neuromorphic sensorimotor loop embodied by monolithically integrated, low-voltage, soft e-skin - Wang, Weichen; Jiang, Yuanwen; Zhong, Donglai; Zhang, Zhitao; Choudhury, Snehashis; Lai, Jian-Cheng; Gong, Huaxin; Niu, Simiao; Yan, Xuzhou; Zheng, Yu; Shih, Chien-Chung; Ning, Rui; et al. (Science (American Association for the Advancement of Science), 2023)
Artificial skin that simultaneously mimics sensory feedback and mechanical properties of natural skin holds substantial promise for next-generation robotic and medical devices. However, achieving such a biomimetic system that can seamlessly integrate with the human body remains a challenge. Through rational design and engineering of material properties, device structures, and system architectures, we realized a monolithic soft prosthetic electronic skin (e-skin). It is capable of multimodal perception, neuromorphic pulse-train signal generation, and closed-loop actuation. With a trilayer, high-permittivity elastomeric dielectric, we achieved a low subthreshold swing comparable to that of polycrystalline silicon transistors, a low operation voltage, low power consumption, and medium-scale circuit integration complexity for stretchable organic devices. Our e-skin mimics the biological sensorimotor loop, whereby a solid-state synaptic transistor elicits stronger actuation when a stimulus of increasing pressure is applied. Our skin provides a protective layer for our bodies, but it also enables detailed sensory feedback and soft interactions with our surroundings. Wang et al . devised a prosthetic electronic skin that incorporates organic semiconductor transistors and has no rigid components, thus mimicking the mechanical aspects of real skin (see the Perspective by Sekitani). At the same time, it can sense external stimuli such as temperature and pressure and encode these stimuli into electrical pulses. The authors showed that the prosthetic skin could evoke neuronal firings at the motor cortex in a rat in vivo, which triggered toe twitching. —Marc S. Lavine A neuromorphic e-skin system simultaneously emulates closed-loop sensory encoding and mechanical softness of natural skin.